a b c = = = lo g 3 2 lo g 2 7 8 ( 2 lo g 2 5 1 ) ( 5 lo g 5 0 . 1 1 ) 2 lo g 2 5 − 5 lo g 5 2
What is the value of a + b + c ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
What about this method
a = l o g 3 2 l o g 2 7 8 = l o g 3 2 l o g 3 3 2 3 = l o g 3 2 l o g 3 ( 2 3 ) 3 1 = l o g 3 2 l o g 3 2 = 1
b = ( 2 l o g 2 5 1 ) ( 5 l o g 5 0 . 1 1 ) = ( 5 1 ) ( 0 . 1 1 ) = ( 5 1 ) ( 1 0 ) = 2
To find c , see that lo g 2 ( 5 ) = lo g 2 ( 5 ) lo g 2 ( 5 ) = lo g 2 ( 5 ) lo g 5 ( 2 ) .
Thus
c = ( 2 lo g 2 ( 5 ) ) lo g 5 ( 2 ) − 5 lo g 5 ( 2 ) = 5 lo g 5 ( 2 ) − 5 lo g 5 ( 2 ) = 0 .
Therefore a + b + c = 1 + 2 + 0 = 3 .
I failed to evaluate c
Me too, failed to calculate c
Failed to calculate C
Problem Loading...
Note Loading...
Set Loading...
Using the exponent and change of base rules, we have that
a = lo g 3 ( 2 ) 3 ∗ lo g 2 7 ( 2 ) = lo g 3 ( 2 ) 3 ∗ lo g 3 ( 2 7 ) lo g 3 ( 2 ) = 1 and b = ( 5 1 ) ( 0 . 1 1 ) = 2 .
To determine c , note that lo g 2 ( 5 ) = lo g 2 ( 5 ) lo g 2 ( 5 ) = lo g 2 ( 5 ) lo g 5 ( 2 ) . Thus
c = ( 2 lo g 2 ( 5 ) ) lo g 5 ( 2 ) − 5 lo g 5 ( 2 ) = 5 lo g 5 ( 2 ) − 5 lo g 5 ( 2 ) = 0 .
Therefore a + b + c = 1 + 2 + 0 = 3 .